Absence of Biomarker-Driven Treatment Options in Small Cell Lung Cancer, and Selected Preclinical Candidates for Next Generation Combination Therapies - Liguori, Nicholas R.; Lee, Young; Borges, William; Zhou, Lanlan; Azzoli, Christopher; El-Deiry, Wafik S. (Frontiers in Pharmacology, 2021)
Lung cancer is the second most common deadly cancer in the United States, and small cell lung cancer (SCLC) accounts for about 15% of all lung cancers. In SCLC, more than other malignancies, the standard of care is based on clinical demonstration of efficacy, and less on a mechanistic understanding of why certain treatments work better than others. This is in large part due to the virulence of the disease, and lack of clinically or biologically relevant biomarkers beyond routine histopathology. While first line therapies work in the majority of patients with extensive stage disease, development of resistance is nearly universal. Although neuroendocrine features, Rb and p53 mutations are common, the current lack of actionable biomarkers has made it difficult to develop more effective treatments. Some progress has been made with the application of immune checkpoint inhibitors. There are new agents, such as lurbinectedin, that have completed late-phase clinical testing while other agents are still in the pre-clinical phase. ONC201/TIC10 is an imipridone with strong in vivo and in vitro antitumor properties and activity against neuroendocrine tumors in phase 1 clinical testing. ONC201 activates the cellular integrated stress response and induces the TRAIL pro-apoptotic pathway. Combination treatment of lurbinectedin with ONC201 are currently being investigated in preclinical studies that may facilitate translation into clinical trials for SCLC patients.